Clinical lipidomics - A community-driven roadmap to translate research into clinical applications - Vvedenskaya, Olga; Holčapek, Michal; Vogeser, Michael; Ekroos, Kim; Meikle, Peter J; Bendt, Anne K (Journal of mass spectrometry and advances in the clinical lab, 2022)
Lipid metabolites, beyond triglycerides and cholesterol, have been shown to have vast potential for applications in clinical applications, with substantial societal and economical value. To successfully evolve from the current research-grade methods to assays suitable for routine clinical applications, a harmonization - if not standardization - of these mass spectrometry-based workflows is necessary. Input on clinical needs and technological capabilities must be obtained from all relevant stakeholders, including wet lab scientists, informaticians and data scientists, manufacturers, and medical professionals. In order to build bridges between this diverse group of professionals, the International Lipidomics Society and its Clinical Lipidomics Interest Group were created. This opinion article is intended to provide an overview of international efforts to tackle the issues of workflow harmonization, and to serve as an open invitation for others to join this growing community.
Keywords: Translation; Lipidomics; Validation; Standardization; Harmonization